DISCUSSION ON “GEOTECHNICAL HAZARDS IN BANGKOK – PRESENT & FUTURE”, BY S. SHIBUYA, S. B. TAMRAKAR AND W. MANAKUL, LOWLAND TECHNOLOGY INTERNATIONAL, 5(1), 95-104 - A. S. Balasubramaniam; N. Phienwej; D. T. Bergado; Y. N. Oh (Lowland Technology International, 2004)
The writers read with great interest the contribution on “Geotechnical Hazard in Bangkok – Present Future”. The writers had a long time interest in the subsidence of Bangkok since 1973 (see Piancharoen and Chuamthaisong, 1976; Piancharoen and Isarangula, 1974; Rammarong, 1974) or so.